2019
DOI: 10.3389/fnmol.2019.00037
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptome Analysis of the Human Tibial Nerve Identifies Sexually Dimorphic Expression of Genes Involved in Pain, Inflammation, and Neuro-Immunity

Abstract: Sex differences in gene expression are important contributors to normal physiology and mechanisms of disease. This is increasingly apparent in understanding and potentially treating chronic pain where molecular mechanisms driving sex differences in neuronal plasticity are giving new insight into why certain chronic pain disorders preferentially affect women vs. men. Large transcriptomic resources are now available and can be used to mine for sex differences to gather insight from molecular profiles using donor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Recent transcriptomics data in animals identified sex-specific PNI responses in DRG ( North et al, 2019 ; Ray et al, 2019 ; Stephens et al, 2019 ; Chernov et al, 2020 ; Mecklenburg et al, 2020 ; Paige et al, 2020 ; Tavares-Ferreira et al, 2020 ; Yu et al, 2020 ). However, sex differences in the immediate post-injury early-response transcriptional events remain not well understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent transcriptomics data in animals identified sex-specific PNI responses in DRG ( North et al, 2019 ; Ray et al, 2019 ; Stephens et al, 2019 ; Chernov et al, 2020 ; Mecklenburg et al, 2020 ; Paige et al, 2020 ; Tavares-Ferreira et al, 2020 ; Yu et al, 2020 ). However, sex differences in the immediate post-injury early-response transcriptional events remain not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory, neuropathic, and idiopathic hypersensitivity and persistent pain conditions often have greater prevalence and symptom severity in women as compared to men ( Unruh, 1996 ; Greenspan et al, 2007 ; Fillingim et al, 2009 ; Mogil, 2012 ; Sorge and Totsch, 2017 ; Boerner et al, 2018 ). Transcriptome RNA-sequencing (RNA-seq)-based analyses of human DRG at baseline ( Ray et al, 2019 ) and in patients with radicular/neuropathic pain ( North et al, 2019 ) highlighted DRG’s central role in sex-specific gene regulation. Likewise, emerging research has revealed sexual dimorphism in rodent DRG transcriptomes in response to peripheral nerve injury ( Stephens et al, 2019 ; Ahlström et al, 2021 ), hyperalgesic priming by interleukin 6 (Il-6; Paige et al, 2020 ), sciatic nerve injection of myelin basic protein (MBP) derived peptides ( Chernov et al, 2020 ), and other stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A threshold of > = 0.75 or < = -0.75 was chosen for the SSMD to identify stably expressed genes that were systematically changing between conditions (Supplementary File 1, Sheet 1). Fold changes were calculated (with a smoothing factor of 0.5 added to both the numerator and denominator 86 for every gene with stable expression in at least one condition for each comparison (Supplementary File 1, Sheet 1).…”
Section: Methodsmentioning
confidence: 99%
“…These points suggest that sex differences in gene expression could be detected in nociceptive pathways of mice and humans. For instance, sex differences in expression of genes involved in pain and inflammation, such as Ntrk1 , Ccl2 , Pdgfr , Traf3 and Vegfa were observed in human tibial nerve 16 . Neuropathic pain conditions are also associated with sex-dependent differential expression of inflammatory genes and transcription factors in human DRG tissues 17 .…”
Section: Introductionmentioning
confidence: 99%